The Cabildo, Justicia, and Regimiento of Arequipa During the «Transcendental Biennium» (1808-1810) - Calderón Valenzuela, Fernando (2017)
The Spanish-American colonies reacted in defense of King Ferdinand VII during the French invasion of Spain in 1808. The events that followed in 1808-1810 exposed the contradictions within the colonial system. In this paper I assess Arequipa’s reaction in this context particularly its Cabildo, which must be understood in connection with the events in neighboring cities—Cuzco, Puno, La Paz, and Potosí—and in the centers of political power—Lima, Chuquisaca, and Buenos Aires. I argue that the loyalism of Arequipa’s population was a strategy to gain autonomy and defend its regional interests while avoiding conflict at the local level. An array of possibilities emerged in that period, as a result of which Spanish-American societies, led by their ruling circles, decided their future.